2001
DOI: 10.1006/anbo.2001.1464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulp Cell Number and Assimilate Availability on Dry Matter Accumulation Rate in a Banana Fruit [ Musa sp. AAA group 'Grande Naine' (Cavendish subgroup)]

Abstract: Fruit position on the bunch (in¯orescence) is an important part of variability in banana fruit weight at harvest, as fruits at the bottom of the bunch (distal fruits) are approx. 40 % smaller than those at the top ( proximal fruits). In this study, the respective roles of cell number and cell ®lling rate in the development of pulp dry weight are estimated. To this end, the source/sink ratio in the plant was altered at dierent stages of fruit development. Leaf shading (reducing resource availability), bunch bag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
4
29
0
2
Order By: Relevance
“…It may be hypothesized that the berries of different positions may not equally access the assimilate pool. The berries from the proximal part of clusters might have a higher priority for receiving assimilate supply, as indicated in banana (Jullien et al 2001a(Jullien et al , 2001b. Overall, the potential roles in berry weight variation of seed number, berry position within a cluster, and within-cluster assimilate supply should be investigated jointly in both seeded and seedless cultivars in order to better explain this variability.…”
Section: Berry Fresh Weightmentioning
confidence: 99%
“…It may be hypothesized that the berries of different positions may not equally access the assimilate pool. The berries from the proximal part of clusters might have a higher priority for receiving assimilate supply, as indicated in banana (Jullien et al 2001a(Jullien et al , 2001b. Overall, the potential roles in berry weight variation of seed number, berry position within a cluster, and within-cluster assimilate supply should be investigated jointly in both seeded and seedless cultivars in order to better explain this variability.…”
Section: Berry Fresh Weightmentioning
confidence: 99%
“…The utilization of cultivars with many female flowers, such as cucumbers with several pistillate flowers per node (multi-pistillate type) or gynoecious and parthenocarpic fruit, increases the rate at which cucumbers can be harvested within a short period (Denna, 1973;Fujieda et al, 1982; vegetative organs (Marcelis, 1992;Schapendonk and Brouwer, 1984) due to changes in sugar metabolism related to variations in fruit load (Boonkorkaew et al, 2011). The distribution of photoassimilates can be attributed to differences in the plant hormone concentrations in fruits (Bangerth, 1989(Bangerth, , 2000Bangerth et al, 2000;Bertin, 1995;Schapendonk and Brouwer, 1984), sink sizes (i.e., the number of cells per fruit) (Bertin et al, 2002;Jullien et al, 2001), or the ontogenetic order of fruit (Egli and Bruening, 2002;Marcelis, 1996). Ganeshaiah and Shaanker (1994) suggest that the autocatalytic or feedback regulation of photoassimilate flow to developing sinks also plays a role in their distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Means followed by the same letter do not differ significantly from each other according to Tukey's test (P≤0.05). Jullien et al (2001b) reported that the maximum diameter reached by a banana is directly related to the number of cells within the radius of the fruit, which in turn is dependent on cell division rates and the duration of cell division phase. This is consistent with the fact that the endogenous level of cytokinin is directly correlated with fruit growth and especially involved in the stimulation of cell division (Kumar et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Large quantities of photosynthates are moved from the source to the sink, i.e., from the leaves to the developing bunches (Mulagund et al, 2015), and the competition for assimilates between fruits determines their size and quality (Jullien et al, 2001b). Thus, strategies to standardize fruit size are of great interest because fruit mass and size (length and diameter) are important commercial criteria for marketing bananas for export.…”
Section: Introductionmentioning
confidence: 99%